Cancer Prevalence in Dera Ghazi Khan; a major concern - Ishaq, Muhammad Uzair; Nawaz, Moeen; Lund, Muhammad Shahwaiz (Journal of the Pakistan Medical Association, 2024)
Dear Mam! In 2020, the International Agency for Research on Cancer (IARC) predicted there would be 19.3 million new cancer cases and 10 million cancer-related deaths globally. In 2018, Pakistan had 173,937 reported cancer cases and 118,442 deaths from cancer. Most cases are from areas in Southern Punjab, Balochistan, and Sindh.1 Over the past five years, cancer cases in Dera Ghazi Khan have been increasing. In 2015, only 68 people died from cancer, but by 2020, the number of deaths rose to 116, the highest recorded so far. In December 2021, there were 157 cancer patients in the region. If preventive measures aren't implemented soon, these cases will continue to rise steadily.2 The reason behind this is that long-term exposure to radium and uranium can lead to severe health issues like oral problems, anaemia, lung diseases, and low white blood cell count. Radon gas, in particular, makes up about half of the public's radiation exposure and can cause various health problems. Radium exposure can result in tumours in the skull, bones, and nose. Additionally, exposure to thorium can increase the risk of cancers such as lung, bone, kidney, and leukaemia. Industries that don't deal with nuclear materials directly require more scientific and regulatory focus because they can still affect nuclear materials, according to the International Atomic Energy Agency in 2013.1 Our healthcare authorities, health ministries, and policymakers must adopt specific measures to prevent chemical and radiation exposure. Factory wastage and unused material should be returned to the mine site for disposal. Samples need to be put in plastic containers. HPGe detectors need to be shielded with thick lead to reduce radiation effectively, especially since their use in agriculture is relatively new. Using plastic containers helps prevent electrical interference and potential issues.1 It's unsafe to have homes and crops in open areas with radiation exposure, as electrical equipment can contaminate food and be breathed in as dust. Phosphate fertilizers should be used less in farming because they can raise the levels of potassium, thorium, and uranium in the soil and plants, affecting people in the long run.3 By using these measures, radiation and chemical exposure will be reduced to a minimum. The increase in cancer cases in Dera Ghazi Khan will also be reduced and brought under control.